Kajian Teknis Pemeliharaan Transformator Arus Pada Gardu Induk Pltu Tanjung Awar – Awar Babat - Rhezal Agung Ananto; Kalam Syamsul Arifin; Ahmad Hermawan; Popong Effendrik (Elposys: Jurnal Sistem Kelistrikan, 2023)
The current transformer is an electric power instrumentation device that functions to change a higher current value to a lower value for protection and measurement purposes. Field conditions and service life cause the current transformer to decrease and not function. Therefore, it is important to do this research to determine the current condition of the current transformer. The method used to obtain current transformer quality indicators is the insulation resistance test method and the tangent delta test method. The results of testing the insulation resistance of current transformers at GI Tanjung Awar Awar Babat in 2020-2021 using the VDE standard (Catalogue 228/4) and IEEE std 43-2000 show that the insulation resistance value of all current transformers has increased by an average of 81900Ω from the previous period but, this value is still in good criteria, namely 170 + 1 MΩ and there is an increase in the current transformer grounding resistance test from the previous period with an average of 0.176 however, according to the PLN book 605.K/DIR/2010 the results of the ground resistance test have good criteria. of < 1. Based on ANSI C 57.12.90 and IEEE C57.152-2013 standards, the tan delta test results are still in good condition because the tan delta value is not more than 0.5%. Current transformer tan delta testing in 2020-2021 has decreased, indicating that the insulation performance of current transformers in 2021 is better than in 2020.